Hannah Arendt and Isaiah Berlin freedom, politics and humanity - Hiruta, Kei, 1981- (Princeton University Press, 2021)
"This book is an exercise in theoretical conversation. Two of the most iconic thinkers of the twentieth century, Hannah Arendt (1906-1975) and Isaiah Berlin (1909-1997) fundamentally disagreed on central issues in politics, history and philosophy. In spite of their overlapping life-stories and experiences as Jewish émigré intellectuals, they held mutual dislike for each other, Berlin going so far as to characterise Arendt as representing 'everything that I detest most'. Drawing on a wealth of new archival material, Kei Hiruta traces the development of the Arendt-Berlin conflict, from their first meeting in wartime New York and the second meeting soon after the establishment of the State of Israel, to their widening intellectual chasm during the 1950s, the Eichmann controversy, their final missed opportunity to engage with each other at a 1967 conference, and Berlin's continuing animosity towards Arendt after her untimely death in 1975. Hiruta juxtaposes political philosophy with intellectual history to examine key issues that simultaneously connected and divided Arendt and Berlin, including the meaning and value of freedom, the nature of totalitarianism and its patterns of emergence, evil and the Nazi Holocaust, human agency and moral responsibility, Zionism, American democracy, Britain's imperial past and its post-war liberal present, and the Hungarian Revolution of 1956. Written in a lively and accessible style, Hannah Arendt and Isaiah Berlin tells, for the first time, the full story of the adversarial relationship between Arendt and Berlin, and draws important lessons for political theory and philosophy today"--